TOURISM STRATEGIES FOR THE UPLIFT OF HOUSEHOLDS IN KERALA WITH SPECIAL REFERENCE TO THEKKADY - JOHN V. DANIEL AND BABY M.D (SAJMMR: South Asian Journal of Marketing & Management Research, 2012)
A tourism strategy for the uplift of households in Kerala is the main scope of this study. This aims to ascertain the opinion of the respondents about the job satisfaction, economics and infrastructure development of locality through tourism. The study covers socio-cultural , economic and negative impacts of tourism in Thekkady, a renowned Wild life sanctuary in Kottayam district, Kerala.